"PENGARUH WORK LIFE BALANCE DAN BEBAN KERJA TERHADAP KINERJA PERAWAT DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING (STUDI KASUS DI FASILITAS KESEHATAN KECAMATAN BUNGKU TENGAH, KABUPATEN MOROWALI, SULAWESI TENGAH) - Nur Aisyah; Maria Pampa Kumalaningrum (Kajian Ekonomi dan Bisnis, 2025)
Abstrak Nurses play a crucial role in healthcare, but increasing work demands can lead to stress, especially if the workload increases. Furthermore, work-life imbalance can worsen nurses' performance. This study used a quantitative approach with Wrapper for Partial Least Squares (WrapPLS). Data were collected through questionnaires distributed to 143 nurses at Morowali Regional General Hospital and Bungku Tengah Community Health Center. The results showed that work life balance had a significant negative effect on work stress, while workload had a significant positive effect on work stress. Work life balance also improved nurses' performance, while workload decreased performance, and work stress negatively affected performance. There was a mediating effect between work life balance and performance through work stress, but no mediating effect between workload and performance. These findings emphasize the importance of workload management and providing support in achieving work life balance to improve the effectiveness and quality of nursing services. Kata kunci: Work life balance, workload, work stress, nurse performance, health service management.